KEJADIAN ABSES SEREBRI PADA PASIEN PJB SIANOTIK DI RS DR M DJAMIL PADANG - Diska Yulia Trisiana (Universitas Fort De Kock, 2021)
Abstract Objective : Cyanotic CHD is a congenital disease, insidence tend to increased with time. At M Djamil Hospital there was 85 case in 2013-2015. Brain abscess is the complication that mostly found in patient that can be serious and fatal. The aim of this study is to identify characteristics and factors in the occurence of brain abscess in cyanotic CHD patients. Methods : This was a cross sectional study. Data were collected from medical records of cyanotic CHD patient who admitted at M Djamil Hospital from 2016 to 2018. Bivariate analysis using paired sample T test and chi square. Data were analyzed with SPSS. P value <0.05 were considered to be statistically significant. Result : A total 15 patient (14.5%) brain abscess of 104 cyanotic CHD were found. Majority patient were boys (67.3%). The subjects mean age was 4.95 years and the youngest age was 1 year old. Nutritional status (p=0.009), head circumference (p=0.005), cyanotic spell (p=0.028), blood gas analysis (p=0.005), and outcome (p=0.005) were significant related factors for brain abscess. Hemoglobin (16.65±3.57), leucocyte (18775±7749.28), hematocryte (54.87±7.90), oxygen saturation (59.93±9.21) were statistycally significant. The culture of abscess were no growth. 9 of 15 patient with brain abscess were died. Conclusion : poor nutritional status, microcephaly, cyanotic spell, metabolic asidosis, hemoglobine, leucocytosis, high hematocryte, and low peripheral oxygen saturation were the significant related factors to brain abscess in cyanotic CHD patients. No bacterial growth in abscess culture. Mortality was still high, sixty percent of brain abscess child were died.Keywords: Brain abscess; cyanotic; congenital heart disease. AbstrakTujuan : insiden pasien penyakit jantung bawaan siantoik semakin bertambah. Di RS Dr. M. Djamil Padang terdapat sebanyak 85 kasus selama tahun 2013-2015. Abses serebri merupakan komplikasi yang paling sering ditemukan dan dapat berakibat serius. Penelitian ini bertujuan mengidentifikasi karakteristik dan faktor yang berhubungan dengan kejadian abses serebri pada pasien PJB sianotik. Metode : suatu penelitian cross sectional, dengan pengumpulan data dari rekam medis pasien PJB sianotik di RS Dr. M. Djamil tahun 2016-2018. Analisis bivariate dengan uji T dan chi square. Kemaknaan signifikan pada p value <0.05. Hasil : total sejumlah 104 pasien PJB sianotik, 15 pasien (14,5%) mengalami abses serebri. Jenis kelamin laki-laki 67,3%. Rerata usia 4.95 tahun dan termuda usia 1 tahun. Faktor yang berhubungan signifikan yaitu status gizi (p=0.009), lingkar kepala (p=0.005), cyanotic spell (p=0.028), analisa gas darah (p=0.005) dan outcome (p=0.05). Hubungan signifikan kejadian abses serebri dengan kadar hemoglobin (16.65±3.57), leukosit (18775±7749.28), hematokrit (54.87±7.90), dan saturasi oksigen (59.93±9.21). Pada pemeriksaan kultur abses tidak ditemukan pertumbuhan mikroorganisme. Sebanyak 9 dari 15 pasien meninggal. Kesimpulan : status gizi buruk, mikrosefal, cyanotic spell, asidosis metabolic, kadar hemoglobin, leukosit, hemokonsentrasi, dan saturasi oksigen perifer rendah merupakan faktor-faktor yang berhubungan signifikan dengan kejadian abses serebri pada pasien PJB sianotik. Tidak ada pertumbuhan mikroorganisme pada kultur cairan abses. Mortalitas cukup tinggi, sebanyak 60% pasien meninggal. Kata kunci : abses serebri; penyakit jantung bawaan; sianotik